Determinants of Unverified News Sharing on Social Media and Its Effects on Corporate Image - Zhang, Zhe; Akhter, Shamim; Al-Abyadh, Mohammed Ali; Cong, Phan The (Frontiers in Psychology, 2022)
Social media channels are interactive channels that let users spread content, participate, and generate positive or negative news. In this era of social media (SM), organizations run structured and systematic campaigns to shape their corporate images. The present study examines the role of social consciousness (SC) of employees, entertainment (Ent), and altruism (Alt) on unverified news sharing (UVN) with the mediation of corporate image (CI) and the moderation of workplace stress (WS). We conducted the study on 375 employees of the social media teams in the corporate sector in China. The sampling technique used in this study is convenience sampling. We carried out data analysis using structural equation modeling (SEM) with the help of Smart PLS (Partial Least Square) software. The results reveal that the entertainment and altruism of employees affect UVN. However, the direct negative effect of social consciousness of employees and CI on UVN came out to be insignificant. The findings also show that CI mediates the relationship between the social consciousness (SC) of employees and UVN, altruism and UVN, and entertainment and UVN. The moderating role of WS between CI and UVNis significant. Theoretically, the study contributes to the literature by examining the effect of different determinants of UVN on SM on the role of CI and WS. Practically, the present study provides implications for the managers and the organizations. The study finds that Alt is an essential factor that fosters UVN and CI; therefore, altruistic values of the employees should be instigated to reduce the flow of UVN.